Differential efficacy of olfactory neurospheres from deviated nasal septum and chronic rhinosinusitis patients in regenerating olfactory epithelium - Rong-San Jiang; Chiang-Wen Lee; Yu-Hsuan Lin; Jing-Jie Wang; Jia-Bin Liao; Kuo-Ti Peng; Yao-Chang chiang; Pei-Ling Chi (Stem Cell Research & Therapy)
Abstract Background Olfactory epithelial stem cells hold significant potential for treating olfactory dysfunction by facilitating tissue maintenance and repair. Understanding the inherent qualities of these stem cells is crucial for optimizing their therapeutic efficacy. Methods Olfactory epithelial samples were collected from patients with deviated nasal septum (DNS) and chronic rhinosinusitis (CRS). These were cultured to form olfactory neurospheres (ONS), which were then analyzed for neural stem cell markers, neurotrophic factor production, and their ability to differentiate into olfactory sensory neurons (OSNs). The regenerative efficacy of these ONS was tested in a methimazole-induced hyposmic mouse model, with the effects on cellular senescence, apoptosis, and proliferation in the olfactory epithelium assessed. Results Both DNS- and CRS-derived ONS exhibited neural stem cell characteristics. DNS-ONS displayed superior self-renewal capacity and higher neurotrophic factor production compared to CRS-ONS, which showed impaired OSN maturation and lower neurotrophic factor levels. In vivo, DNS-ONS were more effective in restoring olfaction, as evidenced by reduced cellular senescence, decreased apoptosis, and increased cell proliferation in the OE of methimazole-induced hyposmic mice. Conclusions These findings highlight the importance of selecting the appropriate ONS source for therapeutic applications, with DNS-ONS showing greater promise for olfactory epithelium repair and olfactory function restoration.